(untitled) - Betsis, Andrew (Thành phố Hồ Chí Minh, 2014)
Contents: Preliminary, also known as Preliminary English Test (PET), provides all the exam practice you need. It contains: - four official examination papers that provide authentic exam practice - a helpful overview of the Cambridge English: Preliminary exam to familiarise you with its format - attractive visual...
Keywords: Tiếng Anh,English language; Kỳ thi,Examinations